The influence of firm, industry and concentrated ownership on dynamic capital structure decision in emerging market - Haron, Razali; Nomran, Naji; Abdullah Othman, Anwar Hasan; Md Husin, Maizaitulaidawati; Sharofiddin, Ashurov (Emerald, 2021)
Abstract Purpose – This study aims to evaluate the impact of firm, industry level determinants and ownership concentration on the dynamic capital structure decision in Indonesia and analyses the governing theories. Design/methodology/approach – This study uses the dynamic panel model of generalized method of moments-System (one-step and two-step) by using a panel data from 2000 to 2014 to examine the relationship between the determinants and leverage. The results are robust to the various definitions of leverage, heterogeneity, autocorrelation, multicollinearity and endogeneity concern. Findings – Growing firms and firms operating in a highly concentrated industry use high level of debt, taking advantage of the tax shield (trade-off theory). However, if the firms are operating in a highly dynamic environment, they take on less debt as to avoid bankruptcy risk. Firms in Indonesia opt for debt financing perhaps to act as a controlling mechanism to mitigate agency conflicts that may exist between the large controlling shareholders and the minority. Aged and highly profitable firms with high tangible and intangible assets and liquidity level operating in a high dynamic environment follow the pecking order theory. Research limitations/implications – This study does not perform each industry regression individually. All the industries are pooled together, as the main focus of this study is to examine the factors affecting leverage of firms in general without giving particular attention to individual industry. Originality/value – The insights on the impact of ownership concentration and industry characteristics are novel especially on Indonesia, thus fill the gap in the literature.